Study of Ketuhanan Yang Maha Esa Value in Civic Education Through the Culture of Banceuy Indigenious Peoples - Hidayat, Tita Nurmalinasari; Sapriya, Sapriya (Asia Pacific Journal of Management and Education (APJME), 2020)
The Customary Community of Banceuy is one of customary communities in Indonesia that still maintains and preserves local cultural wisdom based on Ketuhanan Yang Maha Esa (The Belief in One and Only God) value to this day. Banceuy Customary Village is located in Subang - West Java. The purpose of this research is to find out why the obstacles in the process of cultural inheritance in Banceuy community are not used as barriers by young people in maintaining their customs and culture, although modernization and globalization have entered into the lives of these people. Besides, this study also aims to know the extent of Civic Education on religious and cultural values. This study used qualitative approach and ethnographic method. Therefore, one of the findings of this study reveals that the obstacles in the process of inheritance are not barriers because Banceuy community has the motto of "Ngindung Ka Waktu Mi Bapa Ka Jaman", which means modernity is followed and tradition is maintained.